2021
DOI: 10.1038/s41598-021-81207-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional abnormality of functional connectivity is associated with clinical manifestations in individuals with intractable focal epilepsy

Abstract: We explored regional functional connectivity alterations in intractable focal epilepsy brains using resting-state functional MRI. Distributions of the network parameters (corresponding to degree and eigenvector centrality) measured at each brain region for all 25 patients were significantly different from age- and sex-matched control data that were estimated by a healthy control dataset (n = 582, 18–84 years old). The number of abnormal regions whose parameters exceeded the mean + 2 SD of age- and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Finally, our results offer a potential explanation for how underlying network-level functional connectivity shapes the therapeutic response to stimulation. Studies have shown that aberrant functional connectivity underlies many neural disorders ( Stam et al., 2007 ; Kaiser et al., 2015 ; Nakai et al., 2021 ; Garrity et al., 2007 ), and that neural stimulation alters network-level functional connectivity ( Yazdan-Shahmorad et al., 2018 ; Keller et al., 2018 ; Huang et al., 2019 ) and can treat neural disorders ( Edwardson et al., 2013 ; Lozano and Lipsman 2013 ). As such, therapeutic response to stimulation may be a direct result of a stimulation-induced change from aberrant to healthy network-level functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our results offer a potential explanation for how underlying network-level functional connectivity shapes the therapeutic response to stimulation. Studies have shown that aberrant functional connectivity underlies many neural disorders ( Stam et al., 2007 ; Kaiser et al., 2015 ; Nakai et al., 2021 ; Garrity et al., 2007 ), and that neural stimulation alters network-level functional connectivity ( Yazdan-Shahmorad et al., 2018 ; Keller et al., 2018 ; Huang et al., 2019 ) and can treat neural disorders ( Edwardson et al., 2013 ; Lozano and Lipsman 2013 ). As such, therapeutic response to stimulation may be a direct result of a stimulation-induced change from aberrant to healthy network-level functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…From schizophrenia to epilepsy, aberrant network-level functional connectivity underlies a variety of neural disorders ( Garrity et al., 2007 ; Nakai et al., 2021 ; Stam et al., 2007 ). As such, the ability to modify network-level functional connectivity would be a profound development toward therapies for neural disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our results o↵er a potential explanation for how underlying network-level functional connectivity shapes the therapeutic response to stimulation. Studies have shown that aberrant functional connectivity underlies many neural disorders [1][2][3]52], and that neural stimulation alters network-level functional connectivity [12,17,18] and can treat neural disorders [6,31]. As such, therapeutic response to stimulation may be a direct result of a stimulation-induced change from aberrant to healthy network-level functional connectivity.…”
Section: Network-level Analysis Of Neural Stimulationmentioning
confidence: 99%
“…From schizophrenia to epilepsy, aberrant network-level functional connectivity underlies a variety of neural disorders [1][2][3]. As such, the ability to modify network-level functional connectivity would be a profound development towards therapies for neural disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused mainly on ALFF, fALFF, or ReHo ( Zeng et al, 2013 ; Zhao et al, 2020 ), and the results were partially inconsistent. Studies on VMHC ( Xu et al, 2014 ; Shi et al, 2021 ), DC ( Liang et al, 2020 ; Nakai et al, 2021 ), and GSCorr are rare or even missing.…”
Section: Introductionmentioning
confidence: 99%